2019
DOI: 10.1101/731182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IRG1 and iNOS act redundantly with other interferon gamma-induced factors to restrict intracellular replication ofLegionella pneumophila

Abstract: 18Interferon gamma (IFNγ) restricts the intracellular replication of many pathogens, but 19how IFNγ confers cell-intrinsic pathogen resistance remains unclear. For example, 20 intracellular replication of the bacterial pathogen Legionella pneumophila in 21 macrophages is potently curtailed by IFNγ, but consistent with prior results, no 22Importance 41 Legionella pneumophila is one example among many species of pathogenic bacteria 42 that replicate within mammalian macrophages during infection. The immune signa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This diverts host metabolism towards aerobic glycolysis (49), indicative of tolerance. IFN potently restricts L. pneumophila intracellular replication in a manner that depends in part on host induction of Nos2 and Irg1 (52). Nos2 and Irg1 were induced in uninfected BMDMs by CoA alone, and induction was further enhanced with CoA/LPS cotreatment (Fig.…”
Section: Coa Enhances Macrophage-dependent Tlr Agonist Anti-tumor Act...mentioning
confidence: 92%
“…This diverts host metabolism towards aerobic glycolysis (49), indicative of tolerance. IFN potently restricts L. pneumophila intracellular replication in a manner that depends in part on host induction of Nos2 and Irg1 (52). Nos2 and Irg1 were induced in uninfected BMDMs by CoA alone, and induction was further enhanced with CoA/LPS cotreatment (Fig.…”
Section: Coa Enhances Macrophage-dependent Tlr Agonist Anti-tumor Act...mentioning
confidence: 92%
“…The mammalian catalytic enzyme IRG1 and its generated metabolite itaconate are only induced during infection and/or inflammation (Basler et al 2006) and were previously described for their antimicrobial activities (McKinney et al 2000, Michelucci et al 2013, Naujoks et al 2016, Nair et al 2018, Price et al 2019. In this study, we addressed the role of IRG1 in immunometabolic host responses during Mtb infection and were able to demonstrate that IRG1 is essential for the outcome of immunopathology, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…by inhibiting succinate dehydrogenase (Lampropoulou et al 2016), regulating Nrf2 activity (Mills et al 2018) and modulating electrophilic stress responses (Bambouskova et al 2018). In turn, those activities are able to influence hostpathogen interactions, as it was shown in macrophages during Legionella pneumophila infection (Naujoks et al 2016;Price et al 2019). More recently, Nair et al showed that IRG1-deficient mice are highly susceptible to Mtb infection, while no aberrant phenotypes were found during influenza A virus or Listeria monocytogenes infection (Nair et al 2018).…”
Section: Introductionmentioning
confidence: 91%